Effect of Dividend Policy, Ownership Managerial, And Company Size on Growth Profit - Ira Damayanti; Nani Mulyani (Jurnal SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi), 2023)
This study aims to prove empirically the effect of dividend policy, managerial ownership, and firm size on earnings growth. This research was conducted in a manufacturing company in the non-primary consumer goods industry sector. The type of research used is quantitative with an associative method approach. The type of data used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (IDX) for the 2017–2021 period. Samples were collected using purposive sampling method. The amount of data collected is 40 observation data. The data was processed using the Eviews 9 Statistical Program to test the hypothesis using multiple regression analysis. The results of the F statistic test show that dividend policy, managereial ownership, and firm size affect earnings growth, while the results of the t-test statistic show that partially dividend policy and firm size affect earnings growth, but managerial ownership has no effect on earnings growth.